Làng cổ truyền Việt Nam - Vũ Ngọc Khánh, GS. (Hà Nội : Thanh niên, 2004)
Bắc Giang; Hà Nam; Hà Nội; Hà Tây; Hà Tĩnh; Hưng Yên; Hải Dương; Nghệ An; Phú Thọ; Quảng Bình; Quảng Ngãi; Thái Bình; Thanh Hoá; Thừa Thiên; Yên Bái.
Keywords: Văn hoá Việt Nam; Làng cổ truyền -- Việt Nam